Kajian Bioekologi dan Strategi Pengelolaan Ekosistem Mangrove : Studi Kasus di Teluk Awur Jepara - Pradana, Oky Yuripa; Soenardjo, Nirwani; Suryono, Suryono (Departemen Ilmu Kelautan, Fakultas PerikanJurusan Ilmu Kelautan, Universitas Diponegoro)
Mangrove ecosystem have an important role in the environment. The ecological values of mangrove Teluk Awur is a place for feeding, nursery and spawning ground mangrove organism. This environment also produce detritus that support the existence of organic matter in the waters around. The purpose of this research was to study the condition of mangroves bioecology and socio-economic conditions for integrated stakeholders strategy and management of mangrove Teluk Awur Jepara. Method used is case study, explorative and descriptive. Data were analyzed using SWOT analysis by weighting or scoring. The result showed Teluk Awur mangrove ecosystem in the categorized into good criteria because of it’s density > 1500 ind/ha. There are 27 mangrove species and various fauna depend their lives on to of Teluk Awur mangrove ecosystems. Management strategies are recommended as the first priority is providing mangrove rehabilitation activities involving the public directly (score 4.125). Second, environmental education and sustainable use of mangrove resources to local communities (score 2.887). Third, rulemaking and standard operating procedure (SOP) specifically management of Teluk Awur mangrove ecosystems by Diponegoro University: Marine Station (score 2.601).